(untitled) (Scientific journal of the Fergana State University, 2024)
The distribution of long-nosed beetles (Curculionidae), their adaptation to food plants, and their feeding spectrum were studied in the Fergana Valley. Researches were carried out in Andijan, Fergana, Namangan regions in the foothills, hills, pastures and agricultural agrocenoses. As a result of observations, 6 species belonging to the Curculionidae family, 2 subfamilies (Lixinae, Entiminae), 4 genera (Lixus, Eustenopus, Cleonis, Sitona) were recorded.